PENGUJIAN MODEL DRIVING CYCLE KENDARAAN HONDA CITY BERBAHAN BAKAR PREMIUM - Mrihardjono, Juli; Sinaga, Nazaruddin (Gema Teknologi, 2011)
Juli Mriharjono, Nazaruddin Sinaga, in this paper explain that a driving cycle model can be used to estimate fuel consumption and exhaust gas emission. Driving cycle varies significantly for traffic conditions. Testing of driving cycle model, for a specific vehicle, is needed so that able to be used as fuel consumption and emissions estimation on real traffics. This paper studied driving cycle model in a laboratory. The EPA standard was reffered as the testing procedure. The vehicle used was Honda City 1.5L fueling with gasoline (premium - in Indonesia). The result shows that driving cycle model profile meets with the EPA standard. Changing gears, which affect to vehicle speed, was not affect significantly to fuel consumption which indicated by constant AFR during the cycle. The factors that cause the difference speed of vehicle were gas pedal operated manually, timing of changing gear, and gear operation time duration. Keywords: Driving cycle, exhaust gas emissions, fuel consumption